2009
DOI: 10.1097/nen.0b013e3181996688
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Roles of the Innate Immune System in the Regulation of Apoptosis and Inflammation in the Brain

Abstract: Central nervous system (CNS) tissues contain cells (i.e. glia and neurons) that have innate immune functions. These cells express a range of receptors that are capable of detecting and clearing apoptotic cells and regulating inflammatory responses. Phagocytosis of apoptotic cells is a nonphlogistic (i.e. noninflammatory) process that provides immune regulation through anti-inflammatory cytokines andregulatory T cells. Neurons and glia express cellular death signals, including CD95Fas/CD95L, FasL, tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(111 citation statements)
references
References 114 publications
2
106
0
3
Order By: Relevance
“…These inflammatory factors could be derived from peripheral blood or be locally generated. In this regard, activation of astrocytes and microglia has been shown to elaborate inflammatory cytokines in the brain [47,48]. In the present study, we showed that GFAP-positive astrocytes were significantly increased in the CA1 and CA3 areas of hippocampus in the diabetic rats, implying that astrocytes were activated under chronic hyperglycemic conditions and could thus affect the neuronal metabolism.…”
Section: Discussionsupporting
confidence: 60%
“…These inflammatory factors could be derived from peripheral blood or be locally generated. In this regard, activation of astrocytes and microglia has been shown to elaborate inflammatory cytokines in the brain [47,48]. In the present study, we showed that GFAP-positive astrocytes were significantly increased in the CA1 and CA3 areas of hippocampus in the diabetic rats, implying that astrocytes were activated under chronic hyperglycemic conditions and could thus affect the neuronal metabolism.…”
Section: Discussionsupporting
confidence: 60%
“…The primary function of these cells is to maintain and restore tissue homeostasis by regulating the balance between the protective and the potentially harmful effects of their activation following stimuli, such as acute brain injury [ 74 ]. Microglia are central to the process of immune regulation in the brain, as the immune response of the CNS depends upon phagocytic and scavenger receptors that distinguish foreign and host-derived molecules [ 75 ]. Microglia are the resident phagocytic cells of the CNS similar to macrophages found in other tissues [ 76 ].…”
Section: Tlrs In Cns Immunitymentioning
confidence: 99%
“…Hence, it is fundamental to rapidly clear the infected cells and limiting bystander effects and to reduce massive neuronal loss. Apoptotic cells must be rapidly cleared from the CNS because they contain neurotoxic proteins and viruses capable of increasing host tissue infection (Griffiths et al, 2009). Apoptotic cells express a range of non-self-molecules termed Apoptotic cell-associated molecular patterns (ACAMPs) on their surface and these molecules include sugars, nucleic acids, ribonucleoproteins and oxidized low density proteins.…”
Section: Phagocytosis and Removal Of Infected Cellsmentioning
confidence: 99%